2007
DOI: 10.1097/wnr.0b013e3282f242d3
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal STC-1 cells respond to five basic taste stimuli

Abstract: STC-1 cells have been established as an enteroendocrine cell line from the small intestine. By monitoring the level of intracellular Ca using a calcium-imaging technique, cellular responses of intestinal STC-1 cells to compounds of five basic tastants were investigated. Although this cell line was known to respond to bitter compounds, we found that compounds of the other four basic tastants also stimulate STC-1 cells. When solutions containing glutamate, sucrose, HCl, or NaCl were applied, the intracellular Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…The T1R1 protein is specific to the umami taste receptor, which is activated by L-AAs, including MSG. Our group and others have also demonstrated the presence of T1R3, ␣-gustducin, and transient receptor potential cation channel, subfamily M, member 5 (TRPM5) in gut tissues, as well as in the STC-1 mouse EEC line (3,13,38,48). Although these signaling components are necessary for the complete functional receptor, they are not specific to the umami receptor and do not specifically identify the capacity for chemosensation of L-AAs.…”
Section: Discussionmentioning
confidence: 93%
“…The T1R1 protein is specific to the umami taste receptor, which is activated by L-AAs, including MSG. Our group and others have also demonstrated the presence of T1R3, ␣-gustducin, and transient receptor potential cation channel, subfamily M, member 5 (TRPM5) in gut tissues, as well as in the STC-1 mouse EEC line (3,13,38,48). Although these signaling components are necessary for the complete functional receptor, they are not specific to the umami receptor and do not specifically identify the capacity for chemosensation of L-AAs.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to bitter tastants, compounds of four other basic tastants also stimulated STC-1 cells. Therefore, it was suggested that the gastrointestinal system can sense all five of the basic taste stimuli, and that it might contain a taste receptor signaling system similar to the oral taste system (17). The expression of T1R taste receptors in mouse enteroendocrine cells has also been reported by Dyer et al (6) and Margolskee et al (12).…”
mentioning
confidence: 77%
“…Stimulation with sweet, umami, or salty compound does not induce the CCK release from STC-1 cells. It was previously reported that STC-1 cells can respond to five basic tastants by using the Ca 2+ -imaging technique (17). First, STC-1 cells were treated with each of three taste ligands of saccharin, Glu-Na (Na-glutamate), and NaCl for 1 h and the incubated buffer (Hank's balanced salt solution, HBSS) of STC-1 cells was applied to CCKAR/HEK cells.…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations